The item (kanna) in Quran- semantical Indication - Arman, Lena; Nuseirat, Jihad (Jordan Journal of Islamic Studies, 2023)
This study handles with the item of (kanna) in the Holy Quran, throughout contextual figurative way.It deals with the semantic development. It also shows the meaning of morphological and grammatical.The study revealed that the material is fit with context and cant be replaced by another word.